A Multimodal Discourse Analysis of Ballet and Romantic Intimacy in the Webtoon "If It’s Okay With You, Teacher" - Naya Amelia Cahya Putri (Jurnal Bahasa, Sastra, dan Studi Amerika, 2026)
This study examined how a digital comic represented dynamic bodily movement and abstract emotional experience within a static visual medium. The object of analysis was the one-shot webtoon If It’s Okay With You, Teacher by Studio Paran (2022), which depicted the transformation of a ballet technician into an emotionally expressive artist. The main problem addressed in this research was the semiotic challenge of visualizing fluid ballet movement and the intangible emotion of first love through static images. This research employed a qualitative approach using Multimodal Discourse Analysis, focusing on Visual Grammar. The analysis explored representational, interactive, and compositional meanings in selected panels, paying particular attention to bodily posture, gaze, implied motion, spatial arrangement, and color composition. The findings showed that the webtoon successfully simulated movement through implied vectors, sequential panel structure, and expressive body orientation, while emotional transformation was conveyed through facial expressions, gaze direction, and gradual shifts in color tone. The vertical-scrolling format further functioned as a semiotic resource that structured narrative rhythm and emotional progression. The study concluded that visual grammar provided an effective framework for understanding how static digital images could construct the illusion of motion and articulate invisible emotional states.